A first draft genome of holm oak (Quercus ilex subsp. ballota), the most representative species of the Mediterranean forest and the Spanish agrosylvopastoral ecosystem “dehesa” - Rey, María-Dolores; Labella-Ortega, Mónica; Guerrero-Sánchez, Víctor M.; Carleial, Rômulo; Castillejo, María Ángeles; Ruggieri, Valentino; Jorrín-Novo, Jesús V. (Frontiers in Molecular Biosciences, 2023)
The holm oak (Quercus ilex subsp. ballota) is the most representative species of the Mediterranean Basin and the agrosylvopastoral Spanish "dehesa" ecosystem. Being part of our life, culture, and subsistence since ancient times, it has great environmental and economic importance. More recently, there has been a renewed interest in using the Q. ilex acorn as a functional food due to its nutritional and nutraceutical properties. However, the holm oak and its related ecosystems are threatened by different factors, with oak decline syndrome and climate change being the most worrying on the short and medium term. Breeding programs informed by selection of elite genotypes seems to be the most plausible biotechnological solution to rescue populations under threat. To achieve this and other downstream analyses, we need a high-quality and well-annotated Q. ilex reference genome. Here, we introduce the first draft genome assembly of Q. ilex using long-read sequencing (PacBio). The assembled nuclear haploid genome had 530 contigs totaling 842.2 Mbp (N50 = 3.3 Mbp), of which 448.7 Mb (53%) were repetitive sequences. We annotated 39,443 protein-coding genes of which 94.80% were complete and single-copy genes. Phylogenetic analyses showed no evidence of a recent whole genome duplication, with high synteny of the 12 chromosomes between Q. ilex and Q. lobata and between Q. ilex and Q. robur. The chloroplast genome size was 142.3 Kbp with 149 protein-coding genes successfully annotated. This first draft should allow for the validation of -omics data as well as the identification and functional annotation of genes related to phenotypes of interest such as those associated to resilience against oak decline syndrome and climate change, and higher acorn productivity and nutraceutical value.